2023
DOI: 10.3389/fnut.2023.1019534
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of sugar sweetened beverages, artificially sweetened beverages and fruit juices and risk of type 2 diabetes, hypertension, cardiovascular disease, and mortality: A meta-analysis

Abstract: IntroductionSugar-sweetened beverage (SSB) intake is associated with an increased risk of cardiometabolic diseases. However, evidence regarding associations of artificially sweetened beverages (ASBs) and fruit juices with cardiometabolic diseases is mixed. In this study, we aimed to investigate the association between the SSB, ASB and fruit juice consumption with the incidence of cardiometabolic conditions and mortality.MethodsRelevant prospective studies were identified by searching PubMed, Web of Science, Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 107 publications
0
12
0
Order By: Relevance
“…Overall evidence suggests that carbohydrate quality plays a more important role in chronic disease outcomes than carbohydrate amount. A series of systematic reviews and meta-analyses of data from large cohort studies have shown that high glycemic index or glycemic load diets (often containing higher amounts of refined grains, such as white rice and white bread, starchy foods such as potatoes, and sugar-sweetened beverages [SSBs]), are consistently associated with increased risk of weight gain, obesity, diabetes, CVD, some cancers, and mortality [60][61][62][63][64], whereas minimally processed grains, legumes, whole fruits, and non-starchy vegetables are protective against these conditions [65][66][67][68]. In a recent longitudinal analysis of changes in carbohydrate intake and long-term weight gain in the NHS and HPFS, increasing dietary glycemic index, glycemic load, and amounts of starch, added sugars, refined grains, and starchy vegetables was associated with greater midlife weight gain.…”
Section: Carbohydrate Quantity and Qualitymentioning
confidence: 99%
“…Overall evidence suggests that carbohydrate quality plays a more important role in chronic disease outcomes than carbohydrate amount. A series of systematic reviews and meta-analyses of data from large cohort studies have shown that high glycemic index or glycemic load diets (often containing higher amounts of refined grains, such as white rice and white bread, starchy foods such as potatoes, and sugar-sweetened beverages [SSBs]), are consistently associated with increased risk of weight gain, obesity, diabetes, CVD, some cancers, and mortality [60][61][62][63][64], whereas minimally processed grains, legumes, whole fruits, and non-starchy vegetables are protective against these conditions [65][66][67][68]. In a recent longitudinal analysis of changes in carbohydrate intake and long-term weight gain in the NHS and HPFS, increasing dietary glycemic index, glycemic load, and amounts of starch, added sugars, refined grains, and starchy vegetables was associated with greater midlife weight gain.…”
Section: Carbohydrate Quantity and Qualitymentioning
confidence: 99%
“…In a meta-analysis of prospective studies, the consumption of sugar-sweetened beverages and artificially sweetened beverages was associated with a 12% and 14% increased risk of hypertension, respectively, indicating a positive and linear dose-response relationship between the consumption of these beverages and the risk of hypertension 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite safety evaluations, several studies suggest potential health risks associated with chronic consumption of ASwt. A WHO systematic review 3 revealed that replacement of ASwt with sugar does not provide a means for weight management in the long-term, and several studies have discovered a positive correlation between long term ASwt consumption and risk of developing cardiovascular disease [5][6][7][8] , type 2 diabetes mellitus 6,[8][9][10][11] , and mortality in adults 6,8,9,12 . Current literature also reveals other concerning associations between ASwt consumption and various routinely observed clinical conditions, including heightened risks of developing cancer [13][14][15] , chronic kidney disease 16,17 , adiposity related diseases 8,9,18,19 , as well as non-alcoholic fatty liver disease 20 .…”
Section: Introductionmentioning
confidence: 99%
“…While regulatory bodies generally consider ASwt safe at recommended intake levels, some observational studies suggest an association between high ASwt consumption and an increased risk of CVD. [5][6][7][8] This study did reveal potential interactions between ASwt, particularly As and Su, with cellular targets (CAPN1, LTA4H, MKNK2, ITGA2, and HDAC1) involved in various physiological processes. Notably, some of these targets are linked to functions relevant to CVD development.…”
mentioning
confidence: 99%